Canine Mammary Tumours: Advances in Classification, Grading and Expression of Biological Markers - Sharma, Aditya; Farooq, Sheikh Uzma (International Journal of Bio-resource and Stress Management, 2022)
Mammary tumours are the most frequently encountered neoplasms in female dogs. Malignant types of canine mammary tumours are more frequent than benign mammarytumours. Due to vast histological diversity of canine mammary tumours their diagnosis is difficult and provides little prognostic information. The presence of cells with enlarged nuclei and prominent nucleoli often leads to the misdiagnosis of mammary carcinoma.Use of a histological grading system may be helpful for classification and prognosis of canine mammary tumours. Immunohistochemistry is an extraordinarily powerful tool in the armamentarium of the diagnostic surgical pathologist. It is widely used in diagnosis of cancers by detection of tumor specific antigens expression. Canine mammary tumours have two histological classification given by WHO, first in 1974 and it is modification occur in 1999. New histological classification of CMTs is based on modification of WHO criteria given by Goldschmidt. In Veterinary science, two slightly different Misdorp and Pen systems (modifications of the human method) are used for histological grading of the canine mammary gland carcinoma. These two grading system is based on the assessment of the three morphological features: tubule formation, nuclear pleomorphism and mitotic counts. Some potential prognostic cellular biomarkers have been investigated for canine mammary tumours, and are frequently used for their detection and prognosis. Most commonly used cellular biomarkers are human epidermal growth factor, progesterone and estrogen receptors, E-cadherin and P-cadherin and proliferation marker Ki67.